2021
DOI: 10.3389/fmicb.2021.587696
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Two Shiga Toxin–Converting Bacteriophages Induced From Environmental Shiga Toxin–Producing Escherichia coli

Abstract: Shiga toxin (Stx), encoded by stx genes located in prophage sequences, is the major agent responsible for the pathogenicity of Shiga toxin-producing Escherichia coli (STEC) and is closely associated with the development of hemolytic uremic syndrome (HUS). Although numerous Stx prophage sequences have been reported as part of STEC bacterial genomes, the information about the genomic characterization of Stx-converting bacteriophages induced from STEC strains is relatively scarce. The objectives of this study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…We showed that older adults with MCI had higher abundance of Lactococcus phage ul36 which specifically regulates the probiotic bacteria like Lactococcus lactis (a common yogurt culture) [ 44 ] and may diminish their abundance in the gut, which may ultimately be detrimental for gut-brain axis. On other hand, certain bacteriophages exhibit prophage-like properties, such as Stx2 converting phage 1717, which functions as a mobile genetic element in bacterial genome containing crucial genes associated with bacterial pathogenesis [ 61 ]. The virome signatures detected in the present study were highly variable, and their precise role in age-related cognitive decline remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that older adults with MCI had higher abundance of Lactococcus phage ul36 which specifically regulates the probiotic bacteria like Lactococcus lactis (a common yogurt culture) [ 44 ] and may diminish their abundance in the gut, which may ultimately be detrimental for gut-brain axis. On other hand, certain bacteriophages exhibit prophage-like properties, such as Stx2 converting phage 1717, which functions as a mobile genetic element in bacterial genome containing crucial genes associated with bacterial pathogenesis [ 61 ]. The virome signatures detected in the present study were highly variable, and their precise role in age-related cognitive decline remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12,529,574 and 6,694,250 sequence reads were generated for phages S4lw and D5lw, respectively. The phage genome assembly and annotation were processed as previously described 21 . First, the high-quality reads were obtained using FASTQC and Trimmomatic with the setting of Q30 and then subjected to the de novo assembly using Megahit (version 1.2.9).…”
Section: Methodsmentioning
confidence: 99%
“…genomes 6 , little information is available about the genomic characterization of Stx phages induced from STEC strains 7 .…”
mentioning
confidence: 99%